Respuesta :
Data:
[tex]x = - 3[/tex] (I)
[tex]y = - 2x + 3[/tex] (II)
Solving: Substitute (I) in (II)
[tex]y = - 2x + 3[/tex]
[tex]y = - 2*(-3) + 3[/tex]
[tex]y = 6 + 3[/tex]
[tex]\boxed{y = 9}[/tex]
[tex]x = - 3[/tex] (I)
[tex]y = - 2x + 3[/tex] (II)
Solving: Substitute (I) in (II)
[tex]y = - 2x + 3[/tex]
[tex]y = - 2*(-3) + 3[/tex]
[tex]y = 6 + 3[/tex]
[tex]\boxed{y = 9}[/tex]
With the first equation solved, all you need to do here is to plug the first equation into the second.
[tex]x=-3\\ y=-2x+3\\ \\ y=-2(-3)+3\\ y=+6+3\\ y=9\\ So\ y\ is\ equal\ to\ 9.[/tex]
[tex]x=-3\\ y=-2x+3\\ \\ y=-2(-3)+3\\ y=+6+3\\ y=9\\ So\ y\ is\ equal\ to\ 9.[/tex]